Evaluation of fitness components in strains of Drosophila mulleri carrying different genotypes for an esterase - Lourenço, Marcelo Ferreira [UNESP]; Ceron, Carlos Roberto [UNESP]; Carareto, Claudia M. A. [UNESP] (My University, 2001)
Several fitness components in strains of Drosophila mulleri carrying the slow or the fast alleles for the major beta esterase (esterase-4) found in this species, as well as in heterozygous flies in which the slow or fast alleles came from one of the parents, were evaluated. Twelve components were analysed including longevity of both virgins and mated males and females, productivity, viability, including the egg-larva, egg-pupa, egg-imago and pupa-imago periods. These parameters were used to estimate the total fitness for each genotype. The best score was reached by individuals having the Est-4S/Est-4S genotype (scored at 1.000), followed by a fitness value of 0.892 presented by the Est-4F/Est-4S genotype (with the fast allele from maternal origin), 0.863 for the Est-4F/Est-4F and 0.842 for the Est-4S/Est-4F genotypes (with Est-4F of maternal origin). These results suggested a higher relative adaptability of the Est-4S/Est-4S genotype followed by the Est-4F/Est-4S hybrid that possessed the allele Est-4S of maternal origin, which was incompatible with predictions of neutral polymorphism.
Keywords: Darwinian fitness; Drosophila mulleri; Esterase polymorphism; Fitness components